A smart, phase transitional and injectable DOX/PLGA-Fe implant for magnetic-hyperthermia-induced synergistic tumor eradication. (1st January 2016) - Gao, Wei; Zheng, Yuanyi; Wang, Ronghui; Chen, Hangrong; Cai, Xiaojun; Lu, Guangming; Chu, Lei; Xu, Chunyan; Zhang, Nan; Wang, Zhigang; Ran, Haitao; Li, Pan; et al.
Graphical abstract: Abstract: Magnetic hyperthermia ablation is a new and minimally invasive modality for localized tumor removal. However, an inadequate ablation dosage can leave a residual tumor or cause a variety of complications. In addition, commonly used magnetic nanoparticles can easily escape from the tumor tissue, which present potential safety problems. In this study, a smart phase transitional and injectable implant based on biocompatible poly lactic-co-glycolic acid (PLGA) implant incorporating magnetic material (Fe powder) and anti-cancer drug (doxorubicin (DOX)) was developed. The magnetic-induced hyperthermia and release efficiency of DOX were evaluated in vitro . Drug release can be controlled under external alternating current magnetic field (AMF). The results of the in vivo tumor therapeutic efficacy showed that when exposed to external AMF, this smart injectable DOX/PLGA-Fe implant could converse magnetic energy into heat and accelerate the release of DOX, which leads to increasing the temperature to achieve tumor coagulative necrosis and accelerating the release of DOX to enhance residual tumor apoptosis. Furthermore, there was no leakage of magnetic material, as demonstrated using real-time ultrasound (US) and computerized tomography (CT) imaging, realizing the guidance and monitoring of tumor therapy. In conclusion, this smart phase transitional and injectable implant DOX/PLGA-Fe has the ability to improve the efficiency of this newly developed minimally invasive magnetic ablation of tumor treatment technique, and will provide a new avenue of developing minimally invasive synergistic tumor therapy.